Agricultural biodiversity enhances capacity to adapt to climate change - Meldrum, G.; Sthapit, S.R.; Rojas, W.; King, O. (2013)
To cope with climate change, smallholder farmers rely on agricultural biodiversity. This was the key message resulting from a recent survey of almost 2,400 smallholder farmers across Bolivia, India and Nepal. The research was coordinated by Bioversity International, in partnership with MSSRF, LI-BIRD, and PROINPA. The survey aimed to build understanding of smallholder farmer perceptions of climate change and their coping strategies to gain insight into the adaptive capacity of their production systems and opportunities to enhance their resilience.